Strongly Singular Convolution Operators on Herz-Type Hardy Spaces with Variable Exponent. (8th August 2019) - Wang, Hongbin; Yan, Dunyan
Abstract : We investigate the boundedness of the strongly singular convolution operators on Herz-type Hardy spaces with variable exponent.